GEOKIMIA BATUAN PENUTUP (OVERBURDEN) BATUBARA UNTUK MEMPREDIKSI POTENSI AIR ASAM TAMBANG DI PIT 1 IUP PWR, DI DAERAH KASAI, KABUPATEN BERAU, KALIMANTAN TIMUR - -, Ahmad Helman Hamdani; -, Yoga Adriana Senjaya (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Geochemical studies of cap rock (overburden) on coal mining can be used as an indicator to predict the potential of acid mine drainage (AMD) not from coal itself. Coal overburden at PIT 1 IUP PWR, East Kalimantan composed by clay rocks. Geochemical measurements whic is carried from overburden samples KSD11 and KSD11H; shows that the overburden-based reference SNI 6597-2011 can be categorized as rock Type 1. Plotting on curve grouping PAF / NAF based on the relationship between pH and PAN PPAN KSD11dan KSD11H site shows all samples including NAF group. Analysis of TCLP (toxicity characteristic leaching procedure) showed that low dissolved ferrous metals (0.6 g / L) while the metal content of calcium and magnesium respectively are 0.23 g / L and 0.47 g / L (Table 4.7). When the calculated total of mole equivalents , calcium and magnesium is greater than the iron dissolved, so that although the acid formed will be neutralized. Thus overburden in Likasi PIT 1 is a type of cap rock that not form acid mine drainage when exposed in water and air, so it does not require special handling to prevent the formation of acid mine drainage